A novel, simple, validated and reproducible instrument for assessing provocation threshold levels in patients with symptomatic dermographism. (23rd April 2013) - Mlynek, A.; Vieira dos Santos, R.; Ardelean, E.; Weller, K.; Magerl, M.; Church, M. K.; Maurer, M.
Summary Background Symptomatic dermographism is a common urticarial condition. There is a need for an objective method to determine the provocation threshold for patients, in order to facilitate individualized diagnosis and treatment. Aim To compare the dermal responses evoked by a new type of dermographometer (FricTest) with those evoked by a spring‐loaded dermographometer (the Dermographic tester). Methods Dermal provocation was performed in 30 patients with symptomatic dermographism and 30 healthy controls. The FricTest consists of six tips of varying length, which are stroked over the skin, while the Dermographic tester has a single tip. The widths and volumes of the resulting weals were measured. Results Both instruments were similar in their ability to produce dermal responses. The weal widths of 1 and 3 mm induced by the FricTest were used as the provocation thresholds to distinguish between patients and controls, and to indicate the different levels of severity within the patient group. Conclusions The FricTest was easy to use and produced an objective response. This simple and inexpensive instrument could be used to individualize diagnosis and treatment of patients with symptomatic dermographism, allowing for better personalized management.